Contrasted agronomical and physiological responses of five Coffea arabica genotypes under soil water deficit in field conditions - Sarzynski, Thuan; Vaast, Philippe; Rigal, Clément; Marraccini, Pierre; Delahaie, Boris; Georget, Frédéric; Nguyen, Chang Thi Quynh; Nguyen, Hung Phi; Nguyen, Hai Thi Thanh; Ngoc, Quyen Luu; Ngan, Giang Khong; Bossolasco, Laurent; et al. (Frontiers in Plant Science, 2024)
Breeding programs have developed high-yielding Coffea arabica F1-hybrids as an adaptation against adverse conditions associated with climate change. However, the response to drought of coffee F1 hybrids has seldom been assessed. A trial was established with five C. arabica genotypes (2 pure lines: Catimor and Marsellesa and 3 F1 hybrids: Starmaya, Centroamericano and Mundo Maya) planted under the leguminous tree species Leuceana leucocephala. Coffee growth, yield and physiological responses were assessed under a rain-fed (control: CON) and a rainfall reduction treatment (RR) for 2 years. The RR treatment created a long-term rainfall deficit in a region with suboptimal temperature similar to those predicted by climate change scenarios. It reduced soil water content by 14% over 2 successive years of production and increased hydric stress of the three F1-hybrids (leaf water potentials averaged -0.8 MPa under RR compared with -0.4 MPa under CON). Under RR, coffee yields were reduced from 16 to 75% compared to CON. Mundo Maya F1 hybrid was most productive and the sole high-yielding genotype capable of sustaining its yield under RR conditions. Our results suggested that its significant increase in fine root density (CON = 300 and RR = 910 root.m -2 ) and the maintenance of photosynthetic rate (2.5 -3.5 μmol CO2 m -2 s -1 ) despite high evaporative demand might explain why this genotype maintained high yield under RR condition. This work highlights a possible drought tolerance mechanism in fruit bearing adult coffee trees where the number of fine root in plants increases to intake more water in order to preserve turgor and sustain photosynthesis at high ETo and therefore conserves high yield in dry conditions.